Exploring Pharmacists' Roles during the 2019-2020 Australian Black Summer Bushfires - Alexandra Moss; Toni Green; Simon Moss; Janique Waghorn; Mary-Jessimine Bushell (MDPI AG, 2021)
Background: Australians are no strangers to sudden natural disasters, such as bushfires. The effects of a natural disaster can devastate local communities and health care services. Currently, limited research has explored the role of the pharmacist during a natural disaster. This study explores the role of the Australian pharmacist during the 2019/2020 Black Summer Bushfires. Methods: Semi-structured phone interviews were conducted with ten community pharmacists who worked through the Black Summer Bushfires whose daily tasks and work environment were directly affected by the bushfires. Thematic analysis using NVivo®, a qualitative data analysis software was conducted. Results: Analysis of the transcripts generated six main themes: collaboration; trauma and mental health; power and communication; acute presentations; triaging and emergency prescribing. Pharmacists worked in close collaboration with doctors and members of the local community. They provided triaging services, timely health advice about chronic health problems, and managed acute issues, including wound and burn management and mental health support in traumatic conditions, sometimes without power and communication amenities. The challenges presented to pharmacists during the bushfires warranted creative and flexible approaches at times. Conclusion: This study highlights the need for mental health support and training for pharmacists, provisional prescribing privileges, and a clearer set of contingency regulations and legislation related to emergencies and natural disasters. Further research is warranted to gain greater insight into the roles undertaken by Australian pharmacists during natural disasters and their autonomy in decision making processes during such times.